2011
DOI: 10.26719/2011.17.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Smoking among Saudi university students: consumption patterns and risk factors

Abstract: Tobacco use is increasing among young people, especially in Gulf nations such as Saudi Arabia. The objectives of this study were to estimate the prevalence and behavioural patterns of tobacco use among undergraduate students at King Saud University, Riyadh, Saudi Arabia during the academic year 2008/09 and investigate factors that influenced their tobacco use. A cross-sectional study was done of a representative sample (n = 6793) of the undergraduate student population using a modified version of the global yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
38
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 12 publications
11
38
4
1
Order By: Relevance
“…We found in our study that the effect of the parents who smoke water-pipe on being a water-pipe smoker is high(22.6%) with OR (4.56), also the effect of the sibling who smoke water-pipe is high(29.17%) with more significant OR (6.63).In addition, a similar finding was reported from Saudi study of smoking tobacco among Saudi university students (11) in which the effect of the parents who smoke water-pipe on being a water-pipe smoker was almost similar(26.22%) and the effect of the sibling who smoke water-pipe(24.7%) is slightly lower significant in compare to our study. Also in our study, the effect of close friends who smoke water-pipe on being a water-pipe smoker is significant (20.3%) but not as significant as what was reported from Saudi study of smoking tobacco among Saudi university students (11) which shows the effect of peer pressure (having a smoking friend) on being a smoker is (32%). Furthermore, there is an interesting finding in our study which is 81.8% of water-pipe smokers are physically active ranging from some light physical activity to Regular hard physical training for competition sports which is not explained by other studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found in our study that the effect of the parents who smoke water-pipe on being a water-pipe smoker is high(22.6%) with OR (4.56), also the effect of the sibling who smoke water-pipe is high(29.17%) with more significant OR (6.63).In addition, a similar finding was reported from Saudi study of smoking tobacco among Saudi university students (11) in which the effect of the parents who smoke water-pipe on being a water-pipe smoker was almost similar(26.22%) and the effect of the sibling who smoke water-pipe(24.7%) is slightly lower significant in compare to our study. Also in our study, the effect of close friends who smoke water-pipe on being a water-pipe smoker is significant (20.3%) but not as significant as what was reported from Saudi study of smoking tobacco among Saudi university students (11) which shows the effect of peer pressure (having a smoking friend) on being a smoker is (32%). Furthermore, there is an interesting finding in our study which is 81.8% of water-pipe smokers are physically active ranging from some light physical activity to Regular hard physical training for competition sports which is not explained by other studies.…”
Section: Discussionsupporting
confidence: 88%
“…A study was conducted in KSU has conclude that the prevalence of tobacco smoking among students is 14.5% (11). Furthermore, tobacco (in both forms of cigarette and water pipe smoking) has a very significant effect on the health.…”
Section: Rationalementioning
confidence: 99%
“…The study also found a strong association between male and female smoking status and khat use of students, khat use or smoking of friends, and family members who smoke. The impact of peers on cigarette smoking and substance use has been found elsewhere and is well documented in the findings of some studies in KSA [10, 18] and Arabic countries [8, 17]. Family also has an impact on tobacco use; the smoking habits of family members had a statistically significant effect on the smoking habits of their offspring or siblings.…”
Section: Discussionmentioning
confidence: 58%
“…Meta-analysis results revealed that smoking frequency among male and female students in Iran's universities was 19.8% (17.7 -21.9) and 2.2% (1.4 -3.02), respectively. The prevalence of cigarette smoking in university students was 18.5 % in Turkey (18), 24% in Pakistan (19), and 14.5% in Saudi Arabia (20).…”
Section: Discussionmentioning
confidence: 99%